Double compression-expansion engine (DCEE) fueled with hydrogen: Preliminary computational assessment - Rafig Babayev; Arne Andersson; Albert Serra Dalmau; Hong G. Im; Bengt Johansson (Transportation Engineering, 2022)
Hydrogen (H2) is currently a highly attractive fuel for internal combustion engines (ICEs) owing to the prospects of potentially near-zero emissions. However, the production emissions and cost of H2 fuel necessitate substantial improvements in ICE thermal efficiency. This work aims to investigate a potential implementation of H2 combustion in a highly efficient double compression-expansion engine (DCEE). DICI nonpremixed H2 combustion mode is used for its superior characteristics, as concluded in previous studies. The analysis is performed using a 1D GT-Power software package, where different variants of the DICI H2 and diesel combustion cycles, obtained experimentally and numerically (3D CFD) are imposed in the combustion cylinder of the DCEE. The results show that the low jet momentum, free jet mixing dominated variants of the DICI H2 combustion concept are preferred, owing to the lower heat transfer losses and relaxed requirements on the fuel injection system. Insulation of the expander and removal of the intercooling improve the engine efficiency by 1.3 and 0.5%-points, respectively, but the latter leads to elevated temperatures in the high-pressure tank, which makes the selection of its materials harder but allows the use of cheaper oxidation catalysts. The results also show that the DCEE performance is insensitive to combustion cylinder temperatures, making it potentially suitable for other high-octane fuels, such as methane, methanol, ammonia, etc. Finally, a brake thermal efficiency of 56% is achieved with H2 combustion, around 1%-point higher than with diesel. Further efficiency improvements are also possible with a fully optimized H2 combustion system.